IMG-16. Non-invasive metabolic imaging of response to therapy in diffuse midline gliomas. (3rd June 2022) - Batsios, Georgios; Taglang, Celine; Tran, Meryssa; Gillespie, Anne Marie; Nazarian, Javad; Mueller, Sabine; Viswanath, Pavithra
Abstract: Diffuse midline gliomas (DMGs) are universally lethal pediatric tumors that are defined by the presence of histone H3K27 alterations. The infiltrative nature and anatomical location of these tumors prohibit surgical resection. Radiotherapy, which is standard of care, does not significantly enhance long-term outcome. Novel therapies are sorely needed for DMG patients. Imipridone drugs ONC201 and ONC206 have demonstrated anti-tumor activity in preclinical cancer models, including DMGs and have shown promise in pilot studies in DMG patients. Successful clinical deployment of imipridones requires the identification of companion imaging biomarkers that report on response to therapy. Magnetic resonance spectroscopy (MRS) is a safe, non-radioactive, non-invasive method of imaging metabolism in vivo . 1 H-MRS assesses steady-state metabolite levels and is used in clinics. 2 H-MRS following administration of 2 H-labeled substrates is a novel, clinically translatable method of imaging metabolic pathway activity. Our results indicate that treatment of SF7761 DMG cells with ONC206 causes a significant reduction in 1 H-MRS-detectable lactate, glutamate, glutathione and phosphocholine, pointing to inhibition of glycolysis, oxidative phosphorylation, redox and phosphatidylcholine biosynthesis respectively. Examination of [6, 6'- 2 H]-glucose metabolism using 2 H-MRS indicates that lactate production from [6, 6'- 2 H]-glucose is significantly reduced in ONC206-treated SF7761 cells relative to controls. We then investigated the effect of ONC206 on mice bearing orthotopic SF8628 DMG tumors. At day 7 following the treatment onset, at a timepoint when no change in tumor volume can be observed by anatomical imaging, in vivo 1 H-MRS-detectable lactate and total choline are reduced relative to day 0. Collectively, our studies indicate that imipridones induce alterations in DMG metabolism that can be leveraged for non-invasive 1 H- and 2 H-MRS-based imaging of response to therapy. By providing clinicians with an early readout of treatment response prior to anatomical changes, our biomarkers will enable early assessment of treatment response and, thereby, clinical translation of these promising therapeutics.